From Social Media Engagement to Business Growth: Exploring the Dynamics of Digital Consumer Behavior - Sitta Kusuma (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study explores the role of consumer engagement on social media in driving business growth, focusing on emotional and social interactions as key contributors to performance. Engagement activities such as liking, commenting, and sharing branded content were shown to significantly enhance sales, strengthen customer loyalty, and improve brand visibility. Using a mixed-method design combining online surveys and semi-structured interviews with businesses, the research found that active interaction with brand content fosters stronger purchase intentions and long-term loyalty. The findings further emphasize the role of social influence, noting that recommendations and endorsements from friends, peers, and influencers increase the impact of engagement on consumer decisions. Companies that demonstrate transparency and responsiveness in digital communication are more likely to build trust, which acts as a vital mediator linking engagement behaviors to business growth. This suggests that trust is not merely a secondary outcome but a central mechanism in the engagement–performance relationship.From a managerial standpoint, the study highlights the importance of producing relatable and engaging content tailored to target audiences, utilizing the reach of social networks and influencers, and practicing authentic, transparent communication. These strategies enable firms to build stronger consumer relationships while achieving sustainable growth. For future studies, the research calls for deeper exploration of distinct engagement types, such as cognitive versus emotional responses, across different social media platforms. It also suggests examining how emerging technologies, including artificial intelligence and virtual reality, may shape evolving patterns of consumer engagement and their impact on business performance.